Private governance in the biofuel industry - Partzsch, Lena (2010)
Abstract: "The boom of biofuel is placing enormous demands on existing cropping systems, with most crucial consequences in the agro-food sector. For instance, spurred by the increasing use of corn for ethanol, tortilla prices in Mexico suddenly tripled in early 2007. While the United Nations Special Rapporteur on the Right to Food Jean Ziegler is demanding an international five-year ban on producing biofuels to combat soaring food prices, the biofuel industry is responding with first initiatives of private governance and certification. The Roundtable on Sustainable Palm Oil and the Cramer Commission among others have formulated criteria on 'sustainable' biofuel production and processing. The German Environmental Minister plans to impose compulsory blending of only certified biofuel with petrol available at German stations in the near future. This paper explores the legitimacy of private governance and certification by biofuel industry, highlighting opportunities and challenges. There are thr